Synthesis of Copper Nanoparticles Biologically by Conocarpus erectus L. Aqueous Leaves Extract (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Biologically, the nanoparticles of copper synthesized by aqueous leaves extract of Cono- carpus erectus L. The copper nanoparticles appear rapidly with change in color when the leaf extract mixed with CuSO4 (0.1mM). The copper nanoparticles were character- ized by UV Visible Absorption Spectrometer (UV-S), X-Ray Diffraction (XRD), Fourier Transform infrared (FTIR), and Scanning Electron Microscopes (SEM). By using UV-S, the wave length was around 400 nm, while the size of copper nanoparticles was around 39 nm characterized by XRD and SEM. The technique of FTIR showed the presence of active sites for alcoholic, phenolic, amines and other compounds.